Data persistence in planetary surface network using raptor codes and probabilistic broadcasting - Bo Kong; Gengxin Zhang; Wei Zhang; Dongming Bian; Zhidong Xie (International Journal of Distributed Sensor Networks)
This article investigates the data persistence problem in the planetary surface network of interplanetary Internet using the distributed raptor codes. In order to improve the lifetime of space information and space nodes’ energy efficiency in planetary surface network, we propose an efficient data persistence strategy based on raptor codes and probabilistic broadcasting. Unlike most existing data persistence strategies where the random walks are used to disseminate source packets, the probabilistic broadcasting mechanism is employed in the proposed strategy to reduce the data dissemination cost by exploiting the broadcast property of wireless networks. The decoding performance and data dissemination cost are analyzed. Simulation results validate that the proposed strategy consumes the least data dissemination cost while achieving a better decoding performance compared with other representative strategies.